PENGARUH PENDEKATAN JELAJAH ALAM SEKITAR PADA PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR SISWA - Anggreni, Desy; Tampubolon, Budiman; Sugiharto, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the influenceof the approach of natural surroundings the learning outcomes of IIS 11th grade students of Taman Mulia High School in Kubu Raya Regency. The method used is the experimental method, the form of research used is